Leo Spitzer, Essays in historical semantics. Testimonial volume in honor of Leo Spitzer on the occasion of his sixtieth birthday, February the seventh, 1947. S. F. Vanni, New York, 1948. - Terracini, Benvenuto (El Colegio de México, 2007)
Se reseñó el libro: Essays in historical semantics. Testimonial volume in honorof Leo Spitzer on the occasion of his sixtieth birthday.